Evaluation of the Protective Effects of Cyclosporin A and FK506 on Abnormal Cytosolic and Mitochondrial Ca2+ Dynamics During Ischemia and Exposure to High Glutamate Concentration in Mouse Brain Slice Preparations - Tomoharu Yokoyama; Tadashi Tanoue; Erika Hasegawa; Yukio Ikeda; Shouichi Ohta; Akibumi Omi; Yoshihisa Kudo; Hiroyuki Uchino (Elsevier, 2012)
We examined the protective effects of the immunosuppressants cyclosporin A (CsA) and FK506 on abnormal cytosolic Ca2+ ([Ca2+]c) and mitochondrial Ca2+ concentration ([Ca2+]m) dynamics induced by ischemia or high l-glutamate concentration in mouse brain slice preparations. We used fura-4F and rhod-2 as indicators for [Ca2+]c and [Ca2+]m, respectively, in their acetoxymethylester form. Slice preparations loaded with either of these two indicators were exposed to ischemic artificial cerebrospinal fluid (oxygen- and glucose-deprived medium) for 12 min or to aerobic medium with high l-glutamate concentration (isotonic 20 mM l-glutamate) for 5 min. CsA (1 - 10 μM) showed significant protective effects on the maximum increase in ischemia-induced [Ca2+]c and [Ca2+]m. FK506 (10 μM) showed significant protective effects on the [Ca2+]m increase, but not on the ischemia-induced [Ca2+]c increase. Both immunosuppressants showed almost equal protective effects on the [Ca2+]c and [Ca2+]m increases induced by high l-glutamate concentration. These results suggest that the protective effects of CsA and FK506 on Ca2+ overloading may be dependent upon the common pharmacological sites of actions relating to their effects as immunosuppressants. The small, but significant depressant effects of these drugs could give us important clues for rescuing critical brain damage induced by Ca2+ overloading. Keywords:: ischemia, glutamate, Ca2+ overloading, cyclosporin A, FK506